2017
DOI: 10.7243/2049-7962-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of circulating annexin A2 in hepatic diseases and hepatocellular carcinoma

Abstract: Background and objectives: Hepatocellular carcinoma (HCC) is the fifth most common malignancy and the third leading cause of cancer related mortality worldwide. The identification of new high-sensitivity and high-specificity markers for HCCis essential. Annexin A2 (ANXA2) plays an important role in the pathogenesis of multiple malignancies particularly HCCs and its expression strongly also affects the outcomes of HCC patients. This study aimed to investigate the clinical utility of hepatic and circulating Anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
4
1
0
Order By: Relevance
“…The ROC curve for ANXA2 for detection of HCC was significant, the cutoff point was 10.1 (ng/ml) with sensitivity of 85.0% and specificity of 85.0%. These results are compatible with El-Gezawy et al who reported for early stage HCC, ANXA2 (optimal cutoff of 24.99 IU/ml), higher sensitivity, and specificity (79.34% and 85.56% respectively) than those of AFP (optimal cutoff of 5.96 IU/ml) (67.78% and 59.85% respectively) [18]. The ANXA2 mRNA expression level was obviously, significantly higher and over expressed in HCC tissues rather than in the other patient groups.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The ROC curve for ANXA2 for detection of HCC was significant, the cutoff point was 10.1 (ng/ml) with sensitivity of 85.0% and specificity of 85.0%. These results are compatible with El-Gezawy et al who reported for early stage HCC, ANXA2 (optimal cutoff of 24.99 IU/ml), higher sensitivity, and specificity (79.34% and 85.56% respectively) than those of AFP (optimal cutoff of 5.96 IU/ml) (67.78% and 59.85% respectively) [18]. The ANXA2 mRNA expression level was obviously, significantly higher and over expressed in HCC tissues rather than in the other patient groups.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, ANXA2 level was found to be significantly higher in early HCC patients than chronic hepatitis C patients. These results are compatible with El-Gezawy et al who pastulated that ANXA2 was significantly higher in early HCC patients than cirrhotic patients [18]. Shaker et al also reported that ANXA2 was significantly higher in early HCC patients than chronic liver disease (CLD) patients [24].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Zhang et al 32 who dynamically studied the proteins related to hepatic fibrogenesis in various stages (S0-1, S2, and S3-4) through plasma membrane proteomic technology, found that annexin A2 was highly elevated in S4 compared to that S0-1 and concluded that annexin A2 was a valid biomarker for non-invasive diagnosis of hepatic fibrosis. Elgezawy et al 33 also found that the serum annexin A2 level was significantly elevated in liver fibrosis, liver cirrhosis, early and late HCC, but was not elevated in patients with chronic hepatitis compared with the control group ( P < 0.01).…”
Section: Discussionmentioning
confidence: 93%